Functional level during the first 2 years after moderate and severe traumatic brain injury. (15th October 2015) - Sandhaug, Maria; Andelic, Nada; Langhammer, Birgitta; Mygland, Aase
Abstract: Background : Long-term outcomes after TBI are examined to a large extent, but longitudinal studies with more than 1-year follow-up time after injury have been fewer in number. The course of recovery may vary due to a number of factors and it is still somewhat unclear which factors are contributing. Aim : The aim of this study was to describe the functional level at four time points up to 24 months after traumatic brain injury (TBI) and to evaluate the predictive impact of pre-injury and injury-related factors. Design : A cohort study. Setting : Outpatient. Population : Sixty-five patients with moderate ( n  = 21) or severe ( n = 44) TBI. Methods : The patients with TBI were examined with Functional Independence Measure (FIM) and Glasgow Outcome Scale Extended (GOSE) at 3 months, 12 months and 24 months after injury. Possible predictors were analysed in a regression model using FIM total score at 24 months as the outcome measure. Results : FIM scores improved significantly from rehabilitation unit discharge to 24 months after injury, with peak levels at 3 and 24 months after injury ( p  < 0.001), for the whole TBI group and the group with severe TBI. The moderate TBI group did not show significant FIM score improvement during this time period. GOSE scores for the whole group and the moderate group improved significantly over time, but the severe group did not. FIM at admission to the rehabilitation unit and GCS score at admission to the rehabilitation unit were closest to being significant predictors of FIM total scores 24 months after injury ( B  = 0.265 and 2.883, R 2  = 0.39, p  = 0.073, p  = 0.081). Conclusion : FIM levels improved during the period from rehabilitation unit discharge to 3 months follow-up; thereafter, there was a 'plateauing' of recovery. In contrast, GOSE 'plateauing' of recovery was at 12 months. Clinical rehabilitation impact : The study results may indicate that two of the most used outcome measures in TBI research are more relevant for assessment of the functional recovery in a sub-acute phase than in later stages of TBI recovery.